The Effect of Smartphone on the Reading Comprehension Proficiency of Iranian EFL Learners. (3rd August 2015) - Gheytasi, Maryam; Azizifar, Akbar; Gowhary, Habib
Abstract: Smart phones have turned into an everyday object for teenagers and many believe that these can be used to facilitate the language learning process. The extended band-with as well as the possibility of installing different apps on these smart phones has opened new opportunities for learners to better utilize these technologies for learning and comprehending different contents of language. The current study tries to investigate the impact of using such devices on increasing the reading comprehension competency of English language learners in the city of Ilam, Iran. In order to realize this objective, a sample of 40 high school students (boys and girls) in Ilam Mojtama Fani Tehran English language institute was selected. The participants were divided into two groups; namely experimental and control. Using pre-test and post-test as well as the SPSS software application, the study evaluated the difference in scores of these groups regarding the reading comprehension capability. The results show a significant difference between the experimental and control group following a month of using the application.